A bibliometric analysis of publications on obsessive–compulsive disorder using VOSviewer - Tang, Yimiao; Lu, Xuewen; Wan, Xin; Hu, Maorong (Frontiers in Psychiatry, 2023)
In recent years, there are more and more studies on OCD, but there are few literatures on OCD bibliometric analysis. We use VOSviewer to conduct a bibliometric analysis of OCD and summarize the current research status and future development direction of OCD. We use VOSviewer to analyze the scientific publications from 2000 to 2022 in the OCD field retrieved from the Web of Science Core Collection (WoSCC) database for further visual analysis. We analyzed publication results, journals, countries/regions, institutions, authors, country citations, hot topics, and research frontiers from the 24,552 publications retrieved. This paper integrates the bibliometric information on current research status and emerging trends in the field of OCD. These findings provide valuable insights for the further development of OCD.